EVALUASI KUALITAS LINGKUNGAN PERMUKIMAN DI BANTARAN SUNGAI GAJAH WONG KOTA YOGYAKARTA - , ELITA PUTRI RAHMAWATI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Riverbank refers to the space stretched from the edge of riverbed to the inner side of embankment, which also acts as part of the river borderline. In Yogyakarta City, the reality did not correspond to the regulation regarding river borderline area alongside Gajah Wong River. This is shown by settlements that dominate the land use along the riverbank. Government considers the issue related to the riverbank settlements as quantity problem. However, in deeper view, the problem on riverbank settlements is about not only quantity, but also quality of the neighborhood. Riverbank settlements are not something which can easily be demolished and replaced by vertical housing units. The problem leads further to quality issue, which can only be solved by creating good quality neighborhood along the riverbank. This research aimed to measure and find factors influencing neighborhood quality along Gajah Wong riverbank in Yogyakarta. Method use in this study is explanatory case-study with bigger proportion on deductive than on inductive feature. The result of this research is a conclusion that neighborhood along Gajah Wong riverbank have mayority qualities average. Yet the variables of IPAL (waste water treatment plant) and drinking water consecutively got bad score at every level of neighborhood quality study. Furthermore, this research found two factors which affect neighborhood quality alongside the riverbank: the existence of vacant land and awareness from people living in the neighborhood.